Media Sosial dan Prospek Muslim Kosmopolitan: Konstruksi & Peran Masyarakat Siber pada Aksi Bela Islam - Syahputra, Iswandi (Jurnal Komunikasi Islam, 2018)
This article discusses Indonesian cyber society activeties and its configuration on social media which considered being able to encourage social movements, for instance Defending Islam Action, subsequently well known as ‘Defending Islam Action 212’. This article argues that netizens' activities on social media turned out to involve various class variants and social status and are able to encourage the ' Defending Islam Action’. Moreover, the social formation and activities of netizens on the social media constitute the prospects for the social construction of the cosmopolitan Muslim community in Indonesia. The portrait of Indonesian cosmopolitan Muslim is seen as a congregation of citizens compelled by their religious awareness, regardless of social, political, economic boundaries and even inter-religiosity which reveres universal principles of humanity.